1971
DOI: 10.1073/pnas.68.7.1530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mouse Karyotype by Quinacrine Fluorescence, and Tentative Assignment of Seven Linkage Groups

Abstract: A karyotype of the mitotic chromosomes of the house mouse has been prepared based upon quinacrine fluorescence patterns. All 19 pairs of autosomes and the X and Y chromosomes have been identified. Examination of the chromosomes of the following translocation stocks, T(11;?)lAld, T(3;?)6Ca, T(2;9)138Ca, T(2;12)163H, and T(9;13)19OCa, have led to the tentative assignments of autosomal linkage groups (LG) Meiotic studies of the house mouse, Mus musculus, have been very informative (1), but mitotic studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…In most of the cells it is clear that no mouse NORs are stained by the Ag-AS method. This is not due to the loss of the mouse chromosomes that carry the structural genes for rRNA (numbers 12,15,18, and sometimes 16 in BALB/c) because chromosomes 15 and 18 are present in high frequency in the hybrids (55-14 and 55-44) that were derived from BALB/c. Furthermore, it is unlikely to be due to the loss of a specific mouse chromosome that does not have an NOR because hybrid 55-84 has copies of every mouse chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In most of the cells it is clear that no mouse NORs are stained by the Ag-AS method. This is not due to the loss of the mouse chromosomes that carry the structural genes for rRNA (numbers 12,15,18, and sometimes 16 in BALB/c) because chromosomes 15 and 18 are present in high frequency in the hybrids (55-14 and 55-44) that were derived from BALB/c. Furthermore, it is unlikely to be due to the loss of a specific mouse chromosome that does not have an NOR because hybrid 55-84 has copies of every mouse chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The BALB/c peritoneal macrophage X HT-1080-6TG hybrid 55-14, for example, has a mean of 76 (range 61-87) human and 18 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) mouse chromosomes. Copies of every human chromosome are present (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators have found difficulty in distinguishing chromosome 9 from 13 (Miller, Miller, Kouri, Allderdiee, Dev, Grewal andHutton 1971, Comittee 1972). Although there is no doubt that one of the arms of metacentric chro mosome denoted as marker M5 consists of chromosome 9, however we can not exclude a possibility that part of chromosomes of pair 13 was erroneously classi fied as chromosomes of pair 9.…”
Section: Resultsmentioning
confidence: 99%